Research on Method of Intelligent Mobile Internet Pipeline Deployment Strategy - Jiaojiao Ren; Jun Zhao (Dianxin kexue)
Policy deployment scheduling methods and strategies of the mobile internet smart pipe structure refinement were systematically studied.The deficiencies of existing methods were analyzed,and on the basis of the existing method,a fine method of intelligent pipeline deployment strategy was presented.